Dor linda: da Pretagogia ao Parangadinkra - encruzilhando cosmossensações com conhecimentos didáticos afrorreferenciados - Ventura, Wagner Maycron (2020)
In this dissertation I problematize the implications of my afro ancestral roots in my teaching practices. From the identification of my Markers of Africanities (PETIT; ALVES, 2015) I trace my formative course as a black person. I compose my "formative narratives" (JOSSO, 2010) guided by the notions of the person's vital formation cycles, living tradition and African cosmosensations brought by African, Afro-Diasporic and decolonial authors. From my Africanities, as a starting point for my teaching paths, I propose the development of ways of cross-referencing, feelings, sensations, emotions and knowledge in creations and Afro-referenced didactic products that favor: the implementation of Law 10.639 / 03; Decoloniality to the school curriculum and the strengthening of afro-affiliation among teachers and Rede Municipal de Fortaleza, more specifically the in the Curió neighborhood.